Strategi Penetapan Harga pada Dual-channel Supply Chain dengan Mempertimbangkan Diskon dan Layanan Penjualan - Rahmania, Rizky Astari; Aisyah, Safira Nur; Agata, Novelia; Muthi'ah, Aisyah Dewi (Journal of Advanced Technology and Multidiscipline, 2024)
Driven by increasing internet usage, Indonesia is experiencing a significant rise in e-commerce activities, with transactions projected to grow from 66 million to 99 million by 2029. This growth necessitates a hybrid approach combining online and offline sales channels to maximize market coverage. However, this dual-channel strategy poses challenges in pricing, as customer preferences heavily influence purchasing decisions. This study analyzes pricing strategies within a dual-channel supply chain (DCSC). It examines two main scenarios, centralized and decentralized systems, to determine optimal pricing strategies considering in-sales service and discount. The decentralized system employs a Stackelberg game model, where the manufacturer sets prices first, followed by the retailer. A clothing company is used as a practical case study to apply these mathematical formulations. The study highlights how parameter variations such as customer preferences, service, and unit costs influence price. Notably, the decentralized system often results in higher profitability than the centralized approach under specific conditions. Sensitivity analysis further reveals that while some parameters remain stable, customer preferences significantly affect pricing decisions. A preference for online shopping tends to favor a centralized strategy, indicating that coordinated pricing can mitigate channel cannibalization risks. The study underscores the complex interplay between pricing strategies, discounts, and in-sales services in dual-channel supply chains